Semantic Ambiguity Affects Interpretation in Everyday Conversations - Sarah Theodora Wahyuni Lumbantobing; Bernieke Anggita Ristia (Yayasan Bayt Shufiya Nusantara, 2025)
Semantic ambiguity is a pervasive feature of natural language that arises when words, phrases, or sentences carry multiple possible interpretations. This study aims to explore the nature, types, and communicative implications of semantic ambiguity in everyday conversations through a descriptive qualitative approach and library research method. Findings indicate that semantic ambiguity manifests in lexical, structural, and pragmatic forms, which may cause confusion if not resolved using contextual cues, prosodic elements, or clarification strategies. However, ambiguity is not merely a communication obstacle it also serves as a rhetorical device in humor, advertising, indirect speech, and cross-cultural interactions. Understanding how ambiguity operates in language enhances our awareness of context, social dynamics, and cultural variation in meaning-making. This study contributes to the field of linguistics by emphasizing the importance of pragmatic competence and interpretive flexibility in effective communication.